Heparin and Fibrinolysis - Comparison of Subcutaneous Administration of Unfractionated and Low Molecular Weight Heparin - Eriksson, E; Wollter, I M; Christenson, B; Stigendal, L; Risberg, B (Thrombosis and Haemostasis, 1988)
The effects on the fibrinolytic system after a single s.c. bolus injection (at 9 a.m.) of either 5000 IU conventional heparin or 5000 anti-Xa U of a fractionated low molecular weight heparin (Fragmin, KabiVitrum, Sweden) were investigated in 9 healthy volunteers. The effects were compared to those of an injection of normal saline in 6 volunteers. Samples for biochemical analyses were taken regularily during 6 hours after drug or placebo administration.In the coagulation system the following parameters were measured: Activated partial thromboplastin time (APTT), anti- Xa activity, thrombin time and fibrinogen. The fibrinolytic system was monitored by analysing: plasminogen, ɑ2-antiplasmin, fibrinogen) degradation products (FDP), euglobulin clot lysis time (ECLT), tissue plasminogen activator (t-PA) activity, t-PA antigen and plasminogen activator inhibitor (PAI) activity. Injection of the 2 drugs was followed by elevations in APTT and anti-Xa activity, and were more pronounced for Fragmin than heparin. The fibrinolytic system exhibited a diurnal variation with decreasing PAI activity and increasing t-PA activity during the day. Volunteers receiving normal saline (placebo) showed a similar pattern. The results were unrelated to heparin.It is concluded from this study that neither heparin nor Fragmin had any significant effect on the fibrinolytic parameters when measured after a single s.c. bolus injection since the observed variations were within the diurnal range.
Keywords: Unfractionated herpin; Low molecular weight heparin; Fibrinolysis; Tissue plasminogen activator